Papillary cystadenocarcinoma of the sublingual gland - Neil Giblett; Syed Farhan Ahsan; Ahmed Messahel (Elsevier, 2017)
A 68-year-old Caucasian gentleman presented with a 6-month history of a left sided Level I/II neck swelling involving the floor of mouth. MRI revealed a large cystic lesion and histology confirmed a diagnosis of primary papillary cystadenocarcinoma of the sublingual gland.Papillary cystadenocarcinoma was first described in 1991 by the World Health Organisation [WHO], and is a rare malignant neoplasm characterised by cysts and papillary endo-cystic projections.Papillary cystadenocarcinoma arising from the sublingual glands is extremely rare and has the potential to metastasise to cervical lymph nodes. This patient we report was therefore treated with surgical excision and post-operative radiotherapy.